2022
DOI: 10.3390/ani12192592
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond the Shoal: Fish Welfare as an Individual Attribute

Abstract: Welfare is an individual attribute. In general, providing captive nonhuman animals with conditions conducive to good welfare is an idea more easily applied when dealing with few individuals. However, this becomes much harder—if not impossible—under farming conditions that may imply high numbers of animals living in large group sizes. Although this is a problem inherent to intensive animal farming, it is possibly best exemplified in fish farming, for these practices often rely on extremely high numbers. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 193 publications
0
11
0
Order By: Relevance
“…Research also suggests that fish exhibit “behavioural syndromes,” essentially personality traits that are correlated with each other (e.g., Conrad et al, 2011 ; Torgerson-White & Sánchez-Suárez, 2022 ). For instance, in zebrafish (e.g., Ariyomo & Watt, 2012 ; Martins & Bhat, 2014 ), stickleback (e.g., Bell & Sih, 2007 ), and guppies (e.g., Smith & Blumstein, 2010 ), a recurring “bold-aggression syndrome” has been observed.…”
Section: Personality In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…Research also suggests that fish exhibit “behavioural syndromes,” essentially personality traits that are correlated with each other (e.g., Conrad et al, 2011 ; Torgerson-White & Sánchez-Suárez, 2022 ). For instance, in zebrafish (e.g., Ariyomo & Watt, 2012 ; Martins & Bhat, 2014 ), stickleback (e.g., Bell & Sih, 2007 ), and guppies (e.g., Smith & Blumstein, 2010 ), a recurring “bold-aggression syndrome” has been observed.…”
Section: Personality In Fishmentioning
confidence: 99%
“…Furthermore, in fish, the shy-bold dimension is associated with individual variations in both behavioral and physiological responses to stressful stimuli, often referred to as “stress coping styles” (e.g., Castanheira et al, 2017 ; Thörnqvist et al, 2019 ; Torgerson-White & Sánchez-Suárez, 2022 ). These trait variations frequently cluster into two contrasting styles, representing the extremes of a continuous axis.…”
Section: Personality In Fishmentioning
confidence: 99%
“…The authors of the paper Looking beyond the Shoal: Fish Welfare as an Individual Attribute , which was published at Animals Journal last year (Torgerson-White and Sánchez-Suárez 2022 ), reminded us that fishes express considerable individual variation in cognitive abilities, emotions, and preferences, which are linked to personality (Budaev and Brown 2011 ). Despite similar topics were already highlighted before, like in a whole special issue dedicated to the relevance of fish individuality when assessing their physiology, welfare and performance (Gesto et al.…”
Section: Fishes Are Sentient Animals Expressing Individual Responsesmentioning
confidence: 99%
“…To make matters worse, this is clearly the case for farm and some lab conditions, like holding tanks. As pointed out in by Torgerson-White and Sánchez-Suárez ( 2022 ), it is much easier to deal with this issue in conditions where fishes are kept under low densities, because this could be comparable to improving the welfare of animals in zoos or under some lab conditions, with just a few fishes per tank, for example.…”
Section: Dealing With Fish Individualitymentioning
confidence: 99%
“…Based on an extensive literature review, Toscano et al ( 2016 ) suggested that these behavioral traits and their interindividual variations can lead to specialization in foraging behavior. Cortisol levels are indeed highly influential on many traits, including immune response (Zhang et al, 2022 ), reproductive investment (Jiang et al, 2022 ), metabolism (Fernandes Silva et al, 2022 ; Winberg and Sneddon, 2022 ), energy reallocation to cope with stressors (Gorissen and Flik, 2016 ), and the behavioral and cognitive responses (Alfonso et al, 2019 , 2020 ; Torgerson-White and Sánchez-Suárez, 2022 ). Furthermore, it is also important to emphasize that in many animal species, basal and post-stress cortisol levels, as well as behavioral responses, are correlated in such a way that these characteristics are used to identify coping styles (Alfonso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%